1997
DOI: 10.1038/sj.leu.2400878
|View full text |Cite
|
Sign up to set email alerts
|

Chronic malaria and splenic lymphoma: clues to understanding lymphoma evolution

Abstract: In west Africa, splenic lymphoma with villous lymphocytes and hyper-reactive malarial splenomegaly have many clinical and immunological features in common suggesting an aetiopathological link. We hypothesize that in hyper-reactive malarial splenomegaly the dysregulated immune response to repeated malaria infections results in a stimulated, proliferating pool of B cells in which perturbation of cell growth and apoptosis by environmental and other factors promotes the development of SLVL. In Africa these factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 37 publications
0
18
0
1
Order By: Relevance
“…A berrant immune activation induced by chronic infections with Plasmodium falciparum leads to polyclonal B cell activation characterized by the presence of hyperglobulinemia (1), elevated titers of autoantibodies (2,3), and frequent occurrence of Burkitt's lymphoma (4) and splenic lymphoma (5). The mechanisms that lead to this polyclonal B cell activation are poorly understood.…”
mentioning
confidence: 99%
“…A berrant immune activation induced by chronic infections with Plasmodium falciparum leads to polyclonal B cell activation characterized by the presence of hyperglobulinemia (1), elevated titers of autoantibodies (2,3), and frequent occurrence of Burkitt's lymphoma (4) and splenic lymphoma (5). The mechanisms that lead to this polyclonal B cell activation are poorly understood.…”
mentioning
confidence: 99%
“…The dysregulated immune response to long-term carriage of parasites at low levels likely explains the occurrence of HMS and also promotes the development of complications such as marginal zone splenic lymphoma. 8 Experimental studies have shown evidence that Plasmodium spp. invasion proteins bind to uninfected erythrocytes serving as targets for complement-mediated lysis or macrophage phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…In patients from areas of endemicity, a differential diagnosis of malaria from lymphoma becomes a challenge when clinical presentation or potential relapse is accompanied by fever and splenomegaly (2). A few cases of malaria have been reported in patients with diffuse large-B-cell lymphoma (1,15,18), which is often associated with a splenectomy and with febrile neutropenia observed at the time of chemotherapy.…”
Section: Case Reportmentioning
confidence: 99%